Administrative and Legal Principles of Interaction of Customs Posts of the State Fiscal Service of Ukraine with Other State Authorities and Citizens of Ukraine - O. V. Sidorenko (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of administrative and legal principles of interaction of customs posts of the State Fiscal Service of Ukraine with other state agencies and citizens of Ukraine have been studied. The totality of both general scientific and special methods of scientific cognition made it possible to achieve the goal and objectives of the study. The logical and semantic method has assisted to clarify the essence of the concepts of “interaction” and “interaction of customs agencies with other state authorities”. The features of interaction of customs posts of the State Fiscal Service of Ukraine with other entities have been generalized. The content of the intra-system and inter-system interaction of customs posts of the State Fiscal Service of Ukraine with other entities has been highlighted and revealed. It has been emphasized that customs posts interact with other entities in the performance of such functions as fiscal, law enforcement, service, etc. Particular attention has been paid to the peculiarities of interaction of the customs posts of the State Fiscal Service of Ukraine with local state administrations, local self-governments, the Secret Service of Ukraine and other law enforcement agencies, the State Border Guard Service of Ukraine, etc. It has been noted that one of the forms of interaction of the customs posts of the State Fiscal Service of Ukraine with citizens is the consideration of the complaints of citizens by the chief of the customs post about the decisions, actions or inactivity of the employees of the customs post.